Study of reaction mechanism, structural, optical and oxygen vacancy-controlled luminescence properties of Eu-modified Sr2SnO4 Ruddlesden popper oxide - Kumar U.; Upadhyay S.; Alvi P.A. (My University, 2025)
Eu-doped Sr2SnO4 samples were synthesized using conventional ceramic route, followed by calcination at 1000 °C. Rietveld refinement analysis of XRD data indicates that the samples are single phase and crystallized into tetragonal crystal structure. Functional groups and metal-oxygen interaction has been studied using FTIR spectroscopy. The XPS analysis revealed the presence of oxygen vacancy, Sr in Sr2+ and Sn in Sn2+/Sn4+ in sample. The PL spectrum shows five peaks of Eu3+ due to transition 5D0→7F0,1,2,3,4. The transition peaks 5D0→7F0 and 5D0→7F2 found most intense in PL spectra, and their ratio with 5D0→7F1 were increased up to SSE6 and then decreased for SSE10, due to quenching phenomenon. An efficient energy transfer from oxygen vacancy to 5D0→7F0 state leads to enormously increase in their intensity. By utilizing these absorption states and emission states as metastable state, the present sample can be used in UV-filter, UV-detector, and optical device applications. © 2020 Elsevier B.V.